Effectiveness of meticillin-resistant Staphylococcus aureus decolonization in long-term haemodialysis patients: a systematic review and meta-analysis. Issue 3 (November 2015) - Gebreselassie, H.M.; Lo Priore, E.; Marschall, J.
Summary Background Chronic haemodialysis patients are a high-risk population for meticillin-resistant Staphylococcus aureus (MRSA) colonization, which is a precursor of infection. Aim To summarize the effect of nasal (± whole-body wash) MRSA decolonization in haemodialysis patients by means of a systematic review and meta-analysis. Methods We identified eligible studies using Medline, Embase, the Cochrane database, clinicaltrials.org, and conference abstracts investigating the success of MRSA decolonization in haemodialysis patients. For the statistical analysis, we used Stata 13 to express study-specific proportions with 95% confidence intervals. A likelihood ratio test was used to assess inter-study heterogeneity. Findings Six published prospective cohort studies and one study described in a conference abstract met our inclusion criteria. From 1150 haemodialysis patients enrolled in these studies, MRSA was isolated from nasal swabs of 147 (12.8%) patients. Six of the trials used mupirocin nasal ointment and combined it with chlorhexidine body washes for decolonization. The most widely used protocol was a five-day course of mupirocin nasal ointment application three times a day, and chlorhexidine body wash once daily. The pooled success rate of decolonization was 0.88 (95% confidence interval: 0.75–0.95). A likelihood ratio test of the fixed versus the random-effects model showed significant inter-study heterogeneity (P = 0.047). Four of seven studies determined subsequent MRSA infections in 94 carriers overall, two (2%) of which experienced infection. Conclusion The use of mupirocin together with whole-body decolonization is highly effective in eradicating MRSA carriage in haemodialysis patients. The current literature, however, is characterized by a lack of comparative effectiveness studies for this intervention.